Serological survey of foot and mouth disease in cattle in Jos South Local Government area of Plateau State (2011)
A cross-sectional study was conducted in Jos South Local Government Area (LGA) of Plateau State of Nigeria, to determine the seroprevalence of Foot and Mouth Disease (FMD) in cattle, and identifying the potential risk factors associated with the disease. Sera samples were collected from a total of 162 cattle from the cattle population in the study area, and were analysed. The sera were analysed using FMD-NS 3D-ELISA kit at the FMD Laboratory, National Veterinary Research Institute, Vom. Potential risk factors of age, management system and location of the animals were compared with seroprevalence of FMD. Data were analysed using Chi-square test and statistical significance was set at P< 0.05. The overall seroprevalence of FMD obtained was 56.3%. The highest prevalence recorded in Ratya (82.5%) was significantly different (P<0.05) from the prevalence in Du (73.1%), Kara (62.5%), Rantya (66.7%) and Vom (31.2%). Age specific seroprevalence study shows a higher prevalence in Growers, (72.9%) than in Adults (51%) and Young (31.2%). The difference in prevalence among the different age status was found to be statistically significant (P<0.05). A higher seroprevalence was recorded in extensive management system (71%), than in intensive management system (33.3%). The difference between the two was statistically significant (P<0.05). The study showed that FMD is a significant disease in Jos South LGA. Thus, an appropriate control strategy which should involve regulation of cattle movement and vaccination using the circulating virus strain is advocated. A cross-sectional study was conducted in Jos South Local Government Area (LGA) of Plateau State of Nigeria, to determine the seroprevalence of Foot and Mouth Disease (FMD) in cattle, and identifying the potential risk factors associated with the disease. Sera samples were collected from a total of 162 cattle from the cattle population in the study area, and were analysed. The sera were analysed using FMD-NS 3D-ELISA kit at the FMD Laboratory, National Veterinary Research Institute, Vom. Potential risk factors of age, management system and location of the animals were compared with seroprevalence of FMD. Data were analysed using Chi-square test and statistical significance was set at P< 0.05. The overall seroprevalence of FMD obtained was 56.3%. The highest prevalence recorded in Ratya (82.5%) was significantly different (P<0.05) from the prevalence in Du (73.1%), Kara (62.5%), Rantya (66.7%) and Vom (31.2%). Age specific seroprevalence study shows a higher prevalence in Growers, (72.9%) than in Adults (51%) and Young (31.2%). The difference in prevalence among the different age status was found to be statistically significant (P<0.05). A higher seroprevalence was recorded in extensive management system (71%), than in intensive management system (33.3%). The difference between the two was statistically significant (P<0.05). The study showed that FMD is a significant disease in Jos South LGA. Thus, an appropriate control strategy which should involve regulation of cattle movement and vaccination using the circulating virus strain is advocated.